2017
DOI: 10.3389/fnmol.2017.00115
|View full text |Cite
|
Sign up to set email alerts
|

RyR2-Mediated Ca2+ Release and Mitochondrial ROS Generation Partake in the Synaptic Dysfunction Caused by Amyloid β Peptide Oligomers

Abstract: Amyloid β peptide oligomers (AβOs), toxic aggregates with pivotal roles in Alzheimer’s disease, trigger persistent and low magnitude Ca2+ signals in neurons. We reported previously that these Ca2+ signals, which arise from Ca2+ entry and subsequent amplification by Ca2+ release through ryanodine receptor (RyR) channels, promote mitochondrial network fragmentation and reduce RyR2 expression. Here, we examined if AβOs, by inducing redox sensitive RyR-mediated Ca2+ release, stimulate mitochondrial Ca2+-uptake, RO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 72 publications
1
41
0
Order By: Relevance
“…Since our experimental model consists of wild type rats injected with P. gingivalis and examined for the presence of brain Ab amyloid 55 days after bacterial injection, we did not expect yet to detect the presence of accumulated Ab in plaques. Nevertheless, our protocol did detect monomeric forms as well as soluble oligomeric conformations of Ab, which are pivotal to trigger Tau hyperphosphorylation, and neuronal dysfunction, leading to cognitive deficits in AD pathology (39,(86)(87)(88)(89)(90)(91). We show that periodontal infections with the encapsulated serotypes K1 or K2 of P. gingivalis induced neuroinflammation, astrogliosis, cognitive decline, and histopathological signs of AD in the hippocampus, as compared with the less virulent K4 strain and GPA.…”
Section: Detection Of P Gingivalismentioning
confidence: 77%
“…Since our experimental model consists of wild type rats injected with P. gingivalis and examined for the presence of brain Ab amyloid 55 days after bacterial injection, we did not expect yet to detect the presence of accumulated Ab in plaques. Nevertheless, our protocol did detect monomeric forms as well as soluble oligomeric conformations of Ab, which are pivotal to trigger Tau hyperphosphorylation, and neuronal dysfunction, leading to cognitive deficits in AD pathology (39,(86)(87)(88)(89)(90)(91). We show that periodontal infections with the encapsulated serotypes K1 or K2 of P. gingivalis induced neuroinflammation, astrogliosis, cognitive decline, and histopathological signs of AD in the hippocampus, as compared with the less virulent K4 strain and GPA.…”
Section: Detection Of P Gingivalismentioning
confidence: 77%
“…Studies performed by San-Martin et al demonstrated that Ab oligomers promote RyanR2-mediated Ca 2+ release, mitochondrial Ca 2+ entry, ROS generation, and fragmentation of the mitochondrial structural network. It was further shown that RyanR2 knockdown as well as usage of antioxidants reduces Ca 2+mediated noxious effects of Ab oligomers on mitochondrial function (101,102). Some AD models demonstrated intracellular Ab accumulation, which may also take part in ER calcium signaling destabilization (75).…”
Section: Ab and Neuronal Calcium Signalingmentioning
confidence: 99%
“…It was reported that the open probability of the RyR channel is elevated with Ab42 exposure in planar lipid bilayers (147). In the studies carried out by SanMartín et al (148), the Ab-induced Ca 2+ efflux through RyR in hippocampal neurons is prevented by the inhibition of NADPH oxidase, which suggested that oxidative stress may underlie the mechanism. Ab oligomers are likely to increase the expression of RyR, especially RyR3 (149), the most abundant isoform in brain tissue.…”
Section: Causes Of Er Ca 2+ Signal Disordermentioning
confidence: 96%